Pembelajaran Fun Learning dalam Peningkatan Kapasitas Bahasa Inggis Siswa SD di RPTRA Taman Batu Jakarta Selatan - Sunuantari, Manik; Wibowo, Ganjar; Gunawan, Imsar; Aydin, Phoenix Bilal (Universitas Indraprasta PGRI, 2025)
English is an international language used in interactions between nations. The ability to speak English is one of the requirements to enter the global world. As an international language, vocabulary acquisition is not possible instantly. The problem that children often face is limited access to learning and the difficulty of learning foreign languages when children also have to learn the national language, namely Indonesian. The community service activity chosen was to increase the English language capacity of elementary school students in the Child Friendly Open Public Space (RPTRA) Taman Batu Selatan. This activity is intended so that children who live in the Menteng area of South Jakarta have the opportunity to learn English outside of school. This activity is provided for children who have less access to learning English. Learning is carried out with fun learning methods in order to create a pleasant learning atmosphere for participants. The results obtained in this activity show that there is an increase in the number of English words and students begin to understand the importance of mastering English in the global era. Even participants can repeat the learning obtained by sharing stories with other peers.